2011
DOI: 10.1002/jobm.200900429
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Rhodococcus sp. NB5 capable of degrading a high concentration of nitrobenzene

Abstract: An efficient nitrobenzene degrading bacterium strain NB5, which was able to utilize nitrobenzene as a sole source of carbon, nitrogen and energy under aerobic condition, was isolated from activated sludge in an oil refinery at Hangzhou, China. Based on phenotypic features, 16S rDNA gene sequencing and G + C content analysis, strain NB5 was identified as Rhodococcus sp. NB5. Nitrobenzene degradation experiments using high performance liquid chromatograph (HPLC) showed that strain NB5 could tolerate a high nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…NB and inorganic ions were released to the groundwater simultaneously In groundwater environment of the site, the migration process of NB includes convection, dispersion, adsorption, and biodegradation. NB in wastewater can be degraded, assisted by microorganism [33,34]. NB in groundwater biodegradation in different conditions was well fitted by the Monod equation and the q max values varied from 0.018 to 0.046 h −1 [35].…”
Section: Field Test Site Description and Point Scale Samplingmentioning
confidence: 84%
“…NB and inorganic ions were released to the groundwater simultaneously In groundwater environment of the site, the migration process of NB includes convection, dispersion, adsorption, and biodegradation. NB in wastewater can be degraded, assisted by microorganism [33,34]. NB in groundwater biodegradation in different conditions was well fitted by the Monod equation and the q max values varied from 0.018 to 0.046 h −1 [35].…”
Section: Field Test Site Description and Point Scale Samplingmentioning
confidence: 84%
“…The genus Rhodococcus belonged to the phylum Actinobacteria , which is known to be capable of NB biodegradation [2931]. According to Fig 3, the RE of NB was 49.5%-60.3% in the bottom layer; thus, it was concluded that the genus Rhodococcus was the major NB-degrading genus.…”
Section: Resultsmentioning
confidence: 99%
“…zidentyfikowane w ostatnich latach mikro organizmy takie jak: Rhodococcus sp. NB5, zdolny do całkowitej degradacji 1000 mg nitrobenzenu w ciągu 144 h [65] oraz Pseudomonas sp. a3, którego immobilizowane komórki są w stanie degradować 300 mg nitrobenzenu w czasie 10 godzin w obecności dodatkowych związków aromatycznych w postaci aniliny i fenolu [114].…”
Section: Degradacja Nitrobeznezu -Przykład Alternatywnych śCieżek Rozkładuunclassified